2018
DOI: 10.5194/acp-2018-1123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactive nitrogen (NO<sub><i>y</i></sub>) and ozone responses to energetic electron precipitation during Southern Hemisphere winter

Abstract: <p><strong>Abstract.</strong> Energetic particle precipitation (EPP) affects the chemistry of the polar middle atmosphere by producing reactive nitrogen (NO<sub><i>y</i></sub>) and hydrogen (HO<sub><i>x</i></sub>) species, which then catalytically destroy ozone. Recently, there have been major advances in constraining these particle impacts through a parametr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This is slightly more than found by Fytterer et al (2015), who estimated Antarctic ozone depletion of 5-10% using observations from a different set of satellite instruments. Using two independent chemistry-climate models (CCMs), Arsenovic et al (2019) and Pettit et al (2019) showed that only by including EEP were models able to reproduce stratospheric ozone anomalies found in satellite observations. A number of further studies (e.g., Zawedde et al (2016) Together, these suggest that there is need to improve the EEP forcing (the current EEP proxies are known to underestimate precipitating levels, see Nesse Tyssøy et al (2019)) to ensure better representation of ozone variability in the middle atmosphere.…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%
“…This is slightly more than found by Fytterer et al (2015), who estimated Antarctic ozone depletion of 5-10% using observations from a different set of satellite instruments. Using two independent chemistry-climate models (CCMs), Arsenovic et al (2019) and Pettit et al (2019) showed that only by including EEP were models able to reproduce stratospheric ozone anomalies found in satellite observations. A number of further studies (e.g., Zawedde et al (2016) Together, these suggest that there is need to improve the EEP forcing (the current EEP proxies are known to underestimate precipitating levels, see Nesse Tyssøy et al (2019)) to ensure better representation of ozone variability in the middle atmosphere.…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%